Multifold Nanostructuring and Atomic-Scale Modulation of Cobalt Phosphide to Significantly Boost Hydrogen Production - Yu, J.; Wu, X.; Zhong, Y.; Yang, G.; Ni, M.; Zhou, W.; Shao, Zongping (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Water electrolysis is regarded as a green and highly efficient approach to producing high-purity hydrogen, but commercialization of this technology still requires the development of high-performance and affordable electrocatalysts for the hydrogen evolution reaction (HER). Currently, because of its excellent electrical conductivity and good corrosion resistance in acidic media, cobalt phosphide (CoP) has become a representative non-noble-metal HER catalyst despite its inadequate catalytic activity. Herein, a strategy of multiple catalyst-structure engineering, which simultaneously includes doping, nanostructuring, and in situ nanocarbon coating, was employed to significantly improve the HER performance of CoP. CoP with optimized ruthenium doping and covered by ultrathin graphitic carbon shells shows remarkably high HER catalytic behaviour with a low overpotential of only 73 mV at a current density of 10 mA cm-2 and a small Tafel slope of 46 mV dec-1, close to that of the Pt/C benchmark, while maintaining excellent durability. Moreover, the ultrathin graphene shell has a significant positive effect on catalytic activity. This work demonstrates the necessity and validity of multifold structural control, which can be widely used to design various materials for different catalytic processes.